2020
DOI: 10.1177/1060028020971216
|View full text |Cite
|
Sign up to set email alerts
|

A Pharmacokinetic-Pharmacodynamic Analysis to Dose Optimize Daptomycin in Vancomycin-Resistant Enterococcus faecium: Is the Answer Fixed Dosing or Lowering Breakpoints?

Abstract: Background: The optimal daptomycin dose for vancomycin-resistant Enterococcus faecium remains unclear. Dosing of 8 to 12 mg/kg/d has been recommended to improve outcomes, but literature suggests fixed dosing may improve methicillin-resistant Staphylococcus aureus bacteremia pharmacodynamic (PD) targets. Objective: This study sought to evaluate weight-based versus fixed dosing of daptomycin based on pharmacokinetic and PD (PK-PD) targets in vancomycin-resistant E faecium bacteremia. Methods: PK-PD analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Higher rates of microbiological failure and mortality have been reported in BSIs caused by E. faecium strains with daptomycin MIC 3-4 mg/L when treated with daptomycin [20,21]. In fact, two recent studies found that no dose presented an acceptable PTA against a MIC of 4 mg/L in the Monte Carlo simulation [22,23]. When MICs of 2-4 mg/L were analysed, a fixed dose of 1500 mg daily was needed for ≥ 90% PTA, but this dosage carried an undue risk of toxicity as was associated with an increased 24.5-80.5% risk of achieving a Cmin ≥ 24.3 mg/L [24].…”
Section: Discussionmentioning
confidence: 97%
“…Higher rates of microbiological failure and mortality have been reported in BSIs caused by E. faecium strains with daptomycin MIC 3-4 mg/L when treated with daptomycin [20,21]. In fact, two recent studies found that no dose presented an acceptable PTA against a MIC of 4 mg/L in the Monte Carlo simulation [22,23]. When MICs of 2-4 mg/L were analysed, a fixed dose of 1500 mg daily was needed for ≥ 90% PTA, but this dosage carried an undue risk of toxicity as was associated with an increased 24.5-80.5% risk of achieving a Cmin ≥ 24.3 mg/L [24].…”
Section: Discussionmentioning
confidence: 97%
“… 32 Although daptomycin is weight-based, its pharmacokinetics do not scale linearly with weight, and fixed-dose regimens for VRE BSI have been suggested. 33 The evidence for daptomycin use in VRE BSI was established in patients with a median BMIs of 26 kg/m 2 or weights of 50–60 kg, and are not representative of the increased obesity seen in clinical practice. 11 , 13 , 26 Although retrospective data for combined Gram-positive infections have shown no changes in outcomes for using adjusted body weight for daptomycin dosing, 34 specific studies are lacking for VRE BSI.…”
Section: Discussionmentioning
confidence: 99%